Regional prefrontal and hippocampal differences in gray matter volume are linked to the propensity for renewal in extinction learning - Lissek, Silke; Tegenthoff, Martin (Frontiers in Behavioral Neuroscience, 2025)
IntroductionThe renewal effect of extinction describes the reoccurrence of an extinguished response if recall is performed in a context that is not the same as the extinction context. This learning phenomenon is clinically relevant, since it potentially interferes with therapy success for anxiety disorders or phobias. The propensity to show the renewal effect appears to be a stable processing strategy in context-related extinction, associated with higher BOLD activation in hippocampus, ventromedial PFC (vmPFC) and inferior frontal gyrus (IFG) in individuals who show renewal (REN) compared to those who do not (NoREN). However, evidence on a potential relationship between structural properties such as gray matter volume (GMV) in these regions and the propensity to show renewal is lacking.MethodsIn this study, we applied voxel-based morphometry (VBM) to investigate whether individuals with and without a propensity for renewal differ regarding their GMV in extinction-related brain regions, and whether such a difference is linked to the renewal level.ResultsResults revealed differential GMV in REN and NoREN in adjacent subregions of IFG and vmPFC, respectively. Higher GMV in REN was located predominantly in orbital IFG and in BA10 of vmPFC. Higher GMV in NoREN was located predominantly in triangular IFG and in BA 11 of vmPFC. In bilateral anterior cingulate cortex (ACC) and anterior hippocampus, GMV was overall higher in NoREN. In the complete sample, higher GMV in IFG BA 47, vmPFC BA11, bilateral ACC and bilateral anterior hippocampus was associated with less renewal, and partially with a higher error level in extinction learning in a novel context.DiscussionThe findings suggest that higher GMV in several regions active during extinction learning may support a more thorough processing of extinction trials which in turn could be conducive to an extinction recall solely based on recent extinction memory, disregarding context information. In summary, this study provides first-time evidence for a relationship of GMV in of extinction- and renewal-relevant brain regions with behavioral performance during extinction learning and the propensity to show the renewal effect.